PENGARUH SERVICE QUALITY DAN KEPERCAYAAN TERHADAP CUSTOMER RETENTION DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi Pada MS Glow Cabang Situbondo) - Sari, Alfina Dian Ratna; Sari, Lita Permata; Fandiyanto, Randika (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Marketing is an interconnected activity between companies and consumers as a system for generating profits, therefore having the right marketing strategy can improve it, especially as a means of promotion, in this case the development of MS Glow in Situbondo Regency. The purpose of this research is to analyze and test the influence of Service Quality and Trust on Customer Retention with Customer Satisfaction as an Intervening Variable (Study at MS Glow Situbondo Branch. The sampling method was determined by probability sampling. Data analysis and hypothesis testing in the research used Structural Equation Models – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application show that service quality has a significant effect on customer satisfaction; Trust has a significant effect on customer satisfaction; Service quality has a significant effect on customer retention; Trust has no significant effect on customer retention; Customer satisfaction has a significant effect on customer retention; Service quality has a significant effect on customer retention through customer satisfaction; Trust has a significant effect on customer retention through customer satisfaction